Seneca and the idea of tragedy - Staley, Gregory Allan (Oxford University Press, 2010)
The question of why Seneca wrote tragedy has been debated since at least the 13th century. Since Seneca was a Stoic, critics assumed he wrote with the standard Stoic theory of literature as education in philosophy in mind. This book argues that Seneca was influenced by Aristotle's famous defense of tragedy against Plato's critique.